Knowledge and Practices on the Usage of Pesticides among Farmers in Sevanagala, Sri Lanka - N. Roshini; S. L. Jayarathna; N. Madushani; C. U. Wickramasinghe; K. B. Ekanayake; D. M. G. Fernando (Sri Lanka Journal of Medicine)
Introduction: In Sri Lanka, pesticides are widely used in agriculture, and they have both beneficial effects and health hazards. Method: This descriptive cross-sectional study was conducted in Sevanagala Grama Niladhari Division in south-eastern Sri Lanka, to assess the knowledge and practices on usage of pesticides, using an interviewer-administered questionnaire, among farmers who were aged more than 30 years and selected by systematic random sampling. Results and Discussion: In the sample of 210 male farmers, 204 (97%) had received formal school education and only 21 (10%) had received formal training on pesticide use. Many subjects were aware of the health effects of pesticides including renal failure (204, 97%), dizziness (180, 86%), headache (172, 82%) and cancers (166, 79%). Regarding knowledge of pesticide use, 147 (70%) had scored “good” and above, while 62 (30%) had a “moderate” score. The majority of farmers use some kind of protective equipment including protective clothing (149, 71%) and head coverings (129, 61%). The majority of subjects removed contaminated clothes (188, 90%), bathed using soap (181, 86%) and washed hands with soap and water (144, 69%) after spraying. Empty containers were thrown away by 144 (69%). Regarding the storage of empty containers, 203 (97%) subjects store them away from children while 174 (83%) use a storage room for this purpose. However, 3 (1%) subjects store them inside bedrooms. Regarding healthy practices of pesticide use, only 38 (18%) scored “good” or above, while 170 (81%) of the sample were ranked “moderate”. Knowledge of pesticide use and healthy practices showed a weak positive linear correlation (r=0.354, p<0.001). Conclusion: The findings of this study highlight that the farmers in Sevanagala possess a satisfactory level of knowledge regarding the health effects and safe usage of pesticides, but their practices reveal gaps that need attention.